ΟΙ ΨΥΧΟΛΟΓΙΚΕΣ ΕΠΙΠΤΩΣΕΙΣ ΤΗΣ ΠΑΝΔΗΜΙΑΣ SARS-COV-2 - Δούκη, Σταματίνα (Πανεπιστήμιο Πελοποννήσου, 2022)
Introduction: Infectious disease epidemics in recent years have had a significant impact on the general population of the various states, on their physical health, as well as on their mental well-being. Severe Acute Respiratory Syndrome (Sars) in 2002/2003, the 2009 H1N1 flu pandemic, the Middle East Respiratory Syndrome (Mers) and Sars-cov-2 in recent years have had a significant impact on societies of many countries and it had a significant psychological impact on various groups of the population. Aim: The aim of this study is to review and compose the existing international literature, which records the psychological effects of the covid-19 pandemic on various population groups. Methodology: The methodology followed included the search of research data, which were collected through electronic databases PubMed, Google Scholar, Medline, ResearchGate, books, articles and journals. Results: The psychological effects of the covid-19 pandemic on various groups of population, observed to be: anxiety, fear, psychosomatic symptoms, sleep disorders, depressive symptoms, suicidal tendencies, obsessive-compulsive disorder, stigma, abandonment, isolation, and relapse of mental illness. Coping strategies included: policy-making and individual efforts to solve the problem, such as: meticulous cleansing, self-isolation, seeking social support, seeking support through religion, distraction, denial and avoidance. Conclusions: Factors have emerged that can have an aggravating or protective effect on the mental health of individuals and can be valuable information for the formulation of health policies and the design of appropriate interventions and actions, able to respond effectively to the new challenges that arise, both in terms of prevention and and at the coping level. The need for individualized interventions, focused on the individual and his particularities as well as his interaction with the wider social context in which he belongs, was also pointed out.
Αριθμός Εισαγωγής: 013302 cd
Keywords: COVID-19 (Ασθένεια) -- Ψυχολογικές απόψεις; COVID-19 (Ασθένεια) -- Κοινωνικές απόψεις; COVID-19; Ψυχολογικές επιδράσεις; Μολυσματική νόσος; Πανδημία; Στρατηγικές αντιμετώπισης